The Implementation of Curriculum 2013: English Teachers’ Perceptions on Developing Lesson Plan and Teaching Materials - Dwi Bayu Saputra (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2019)
Curriculum 2013 has been implemented in both primary and secondary schools in Indonesia. To execute this, teachers are supposed to be the only medium that has a major role in running this curriculum. However, they do not seem to have well preparations to implement the 2013 curriculum. Some fundamental aspects in this curriculum such as planning lesson and teaching materials need to have more attention in order to run the program well. Moreover, teachers should be well informed regarding these aspects, yet the implementation of 2013 curriculum in English teaching learning is not completely perfect. Considering the issue above, this research aims to investigate English teachers’ perceptions towards developing lesson plans and teaching materials. A questionnaire was used to collect the data about their insights on developing lesson plan and teaching materials. To triangulate the data, this research also administered an interview. The finding indicates that the English teachers tended to feel that structuring lesson plan is not an easy task. They sometimes felt burdensome in modifying the lessons and teaching materials. Besides, 80% of the participants stated that their teaching objectives were achieved after concerning those aspects. The results indicate that teachers needed sufficient knowledge and strong motivation to deal with these important aspects.